Procedure Time of Endovascular Thrombectomy as Performance Measure of Acute Stroke Treatment - Eung-Joon Lee; Han-Yeong Jeong; Jayoun Kim; Nan Hee Park; Min Kyoung Kang; Dongwhane Lee; Jinkwon Kim; Yo Han Jung; Sungwook Yu; Wook-Joo Kim; Han-Jin Cho; Kyungbok Lee; et al. (Neurointervention)
Purpose Procedure time (PT), defined as the time between groin access and vessel recanalization, is a recently recognized predictor of outcomes after endovascular thrombectomy (EVT) for acute ischemic stroke (AIS). However, the factors affecting PT and its potential value as a performance measure of AIS treatment remain unexplored. Materials and Methods Using the Korean Stroke Registry, we compared patients who underwent EVT for AIS from 2018 to 2022 based on 60 minutes PT. We conducted multivariate analysis to investigate whether PT <60 minutes was associated with successful recanalization and good functional stroke outcomes. We also investigated factors that independently predicted PT ≥60 minutes. Furthermore, we determined the cutoff point for PT. Results We analyzed 4,703 patients (mean age: 69.5±11.9, 60.3% male) who underwent EVT. The mean PT was 54.6±36.7 minutes. Multivariate analysis revealed that PT <60 minutes independently predicted a good functional outcome as represented by modified Rankin Scale scores of 0–2 (adjusted odds ratio [aOR]: 1.40, 95% confidence interval [CI]: 1.22–1.59). PT <60 minutes was significantly associated with successful recanalization after adjusting for confounding variables (aOR: 1.66, 95% CI: 1.33–2.07). Moreover, after adjusting for covariates, age≥65 years (aOR: 1.20, 95% CI: 1.05–1.38), onset-to-door time (aOR: 1.03, 95% CI: 1.01–1.04), door-to-puncture time (aOR: 1.05, 95% CI: 1.03–1.06), posterior circulation stroke (PCS) (aOR: 1.13, 95% CI: 1.02–1.28), and smoking (aOR: 1.24, 95%CI: 1.09–1.45) independently predicted PT ≥60 minutes. Finally, the highest aOR for good stroke outcome was observed in the 60-minute cutoff model (aOR: 1.45, 95%CI: 1.27–1.67). Conclusion PT <60 minutes was significantly associated with good functional outcomes. Conversely, PT ≥60 minutes was associated with older age, PCS, smoking, prolonged onset-to-door and door-to-puncture time. Further studies are necessary to develop refining strategies for optimizing PT to improve stroke outcomes.